Leishmanicidal activity of Aspidosperma nitidum Benth. Ex Müll. Arg (Research, Society and Development, 2021)
Drug treatment for leishmaniasis can lead to several adverse reactions, and therapy-resistant isolates of Leishmania have already been found. In this scenario, the search for therapeutic alternatives and alkaloids, isolated from plants belonging to the genus Aspidosperma, has proved to be promising as antiparasitic. The present study evaluated the antipromastigote, amastigote and cytotoxicity activity of the extract and fractions belonging to A. nitidum. The ethanol extract of the shells (EE) was obtained by maceration and submitted to an acid:base partition, with the FN and FA fractions being obtained. In addition, the EE was subjected to fractionation under reflux, obtaining the fractions FrHEX, FrDCL, FrAcOEt and FrMeOH. The antipromastigote activity in L. amazonesis and cytotoxicity to macrophages were evaluated using the viability test (MTT). After the invasion of macrophages by the parasite, the treatment was performed with different sample concentrations during 72 hours, followed by samples staining and reading under the optical microscope. Only FrDCL was moderately active against promastigotes (IC50=105.7 µg/mL). However, EE (IC50 = 23.87 µg/mL) and FA (IC50 = 18.5 µg/mL) were shown to be active against amastigote, whereas in FrDCL (IC50 = 204.5 µg/mL) and FrHEX (IC50 = 143.0 µg/mL) moderate activity was observed. When samples cytoxicity is related to antiamastigote activity, the EE (CC50 = 491.8 µg/mL; IS = 21) seems to be more promising than the FA (CC50 = 209.1 µg/mL; IS = 11). In summary, A. nitidum is promise as a leishmanicide.